Occurrence of MDR and ESBL as respiratory pathogens. - Nikita Naik (International Journal of Life Sciences, 2017)
In recent times, new mechanisms of resistance have resulted in the simultaneous development of resistance to several antibiotic classes creating very dangerous multidrug-resistant (MDR) bacterial strains, known as "superbugs". The indiscriminate and inappropriate uses of antibiotics in outpatient clinics, and in hospitalized patients are the largest factor leading to antibiotic resistance. This dramatic rise in the development of drug resistance, demands new strategies for the control of these strains